2020
DOI: 10.1148/radiol.2020192029
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Status at Single-Phase and Multiphase CT Angiography versus CT Perfusion for Outcome Prediction in Anterior Circulation Acute Ischemic Stroke

Abstract: NEURORADIOLOGYC ollateral status is an important predictor of radiologic and clinical outcome in patients with acute ischemic stroke (AIS) due to anterior circulation occlusions (1,2). Blood flow can reach the ischemic territory through collaterals and may contribute to prolonged penumbral sustenance (3,4). Although digital subtraction angiography is considered the standard modality with which to assess collateral flow (4), it is impractical to use for assessment in an acute setting since it is essential to sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…More importantly, mCTA parameters may provide equivalent hemodynamic information of CTP concerning transit time and blood flow (3,12). Christopher et al (3) found that both mCTA and CTP yielded a similar value for predicting follow-up infarction based on the Alberta Stroke Program Early CT score (ASPECTS) regions in patients with AIS.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, mCTA parameters may provide equivalent hemodynamic information of CTP concerning transit time and blood flow (3,12). Christopher et al (3) found that both mCTA and CTP yielded a similar value for predicting follow-up infarction based on the Alberta Stroke Program Early CT score (ASPECTS) regions in patients with AIS.…”
Section: Discussionmentioning
confidence: 99%
“…We used logistic regression, adjusted for patient age, baseline NIHSS, time from stroke symptom onset to baseline NCCT, baseline ASPECTS, occlusion location, and a dummy variable representing the eight possible combinations of mCTA eligibility (yes vs. no) versus CTP-eligibility (yes vs. no) conditional on treatment type (EVT performed vs. not) to assess the effect on outcome. This model helps generate probabilities for good outcomes for the following eight conditions namely (1) mCTA eligible, CTP eligible, EVT performed; (2) mCTA not eligible, CTP eligible, EVT performed; (3) mCTA not eligible, CTP eligible, EVT performed; (4) mCTA not eligible, CTP not eligible, EVT performed; (5) mCTA eligible, CTP eligible, EVT not performed; (6) mCTA not eligible, CTP eligible, EVT not performed; (7) mCTA not eligible, CTP eligible, EVT not performed; and (8) mCTA not eligible, CTP not eligible, EVT not performed. We deliberately chose to report adjusted rather than unadjusted outcomes since in a non-randomized setting, the latter are subject to substantial confounding by baseline prognostic variables.…”
Section: Methodsmentioning
confidence: 99%
“…Pial collateral status assessment has high specificity if the collaterals are good on a single phase CTA but poor collateral filling could be a false result due to delay in timing of the contrast bolus and consequent arterial filling. 7 Both CTP and mCTA provide time-resolved images that try to address the issue of mistimed bolus contrast influencing assessment of contrast enhanced computed tomography (CT) in patients with acute stroke. 8,9 In CTP, the brain is continuously scanned over 45 to 90 seconds, while in mCTA, three scan cycles are performed over 16 to 20 seconds.…”
Section: Introductionmentioning
confidence: 99%
“…Single-phase collateral scores, however, have been shown to be inferior compared to multiphase scores, because they do not depict the time delay and the spatial extent of collateralization in the late venous phase and, hence, might underestimate the actual collateralization 11]. Multiphase scores also show better correlation with perfusion parameters and clinical outcome [12].…”
Section: Introductionmentioning
confidence: 99%